Acceptability, safety, and clinical outcomes of postpartum intrauterine contraceptive device insertion: a prospective study at a tertiary care hospital - R., Shruthi K.; Kalgudi, Ananda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Contraception is vital in improving the quality of life of women and reducing the maternal mortality and morbidity, occurring due to unplanned pregnancy. During the immediate post-delivery period, women are highly motivated and need an effective method of contraception. The benefits of the postpartum intrauterine contraceptive device (PPIUCD) have to be emphasized to the women Methods: The present study was conducted in the department of obstetrics and gynecology, JSS hospital, Mysore, from June 2021 to June 2024, spanning a period of 3 years. After counseling and consent, Copper T 380A was inserted after delivery. Acceptability, safety, and clinical outcome were studied. Results: Among a total of 14196 deliveries at JSS hospital during the study period, 3107 PPIUCDs were inserted (21.88%). The 2522 among 6258 antenatally counselled women accepted PPIUCD insertion (40.3%), and 2450 (97.14%) got PPIUCD inserted. The 585 (11.68%) out of 5006 women counseled on admission for delivery had PPIUCD inserted. The most common reason for denial of PPIUCD was a family member's objection, followed by the concern about side effects. The 718 (23.10%) women reported complications like excessive bleeding, white discharge per vagina, abdominal pain, and only 2 (0.075%) had spontaneous expulsion of PPIUCD. Conclusions: PPIUCD appears to be a safe and effective method of contraception. All the institutions providing health care to women need to be trained in the correct insertion technique of PPIUCD, counselling of women and family members, to propagate this novel method of contraception, and to motivate the women for continuation of IUCD by providing effective follow-up service.